The next four years: Geographical reflections on the second Trump administration. - Nagel, Caroline; Hopkins, Peter (Geographical Journal, 2025)
In this introductory essay, we reflect on the significance of the re‐election of Donald Trump to the presidency in the United States, and we provide some context for interpreting Trump's second term. Two of Trump's early policy moves—the release of billions of gallons of water from reservoirs in California and the granting of refugee status to Afrikaners—portend four years of politics based on alternative facts, conspiracy theories, and racial grievances. Trump's political agenda has received a significant boost from Silicon Valley billionaires, who are keen to eliminate regulatory bureaucracy. Paradoxically, while allied with high‐tech futurists, Trump's policies hearken to an earlier era of imperialism and settler colonialism. After outlining the basic contours of Trump's agenda, we provide an overview of this special section on the second Trump presidency as viewed by geographers. We conclude by giving attention to themes not covered in this collection, including the Trump administration's attacks on US universities. In this tumultuous time, geographers must communicate their research to a sceptical and distrustful public that has grown weary of liberal policies. This introductory paper reflects on the significance of the re‐election of Donald Trump to the presidency in the United States. It provides context for interpreting Trump's second term, and it provides an overview of the contributions to this special section.